Integrative Research and Learning Model Using a Laboratory-Scale Solar Power Plant Prototype for Vocational Education - Moh. Sulhan; Bakti Indra Kurniawan; Sutoko Sutoko (Universitas Islam Raden Rahmat, Malang, 2026)
Photovoltaic system is an object for growing research since the trend of worldwide energy sources is shifting into renewable ones, especially in tropical regions where solar irradiance reaches optimum throughout the year. However, the implementation of this type of energy source faces a lot of challenges, including complexity in installation and requirement of deep understanding in solar energy conversion. This research is focused on implementing a prototype of photovoltaic system for supporting and improving learning process, particularly in vocational education institutions. By using an easy-to-understand photovoltaic system prototype, it is expected to improve the learning process for vocational students, which eventually makes high-capable human resources to implement the photovoltaic systems. This prototype is proven for increasing lecturer effectiveness in supervising student practices in vocational education institutions, by achieving Likert scale of 4.32 on student perception questionnaire conducted soon after obtaining the results of the technical quantitative measurements.